INANCIAL FEASIBILITY OF CRAB NET CATCHING UNIT IN GALESONG SUBDISTRICT TAKALAR DISTRICT - Yusuf, Djumran; Amiluddin, Amiluddin; RezkiHikmawati, Sri (Torani Journal of Fisheries and Marine Science, 2016)
Appliance catch which is suited for catching existing crab type in coastal territorial water is called the gill net with one sheet or gill net. This research aim to know: (1) kind andinvesment needed at arrest unit crab net, and (2) financial feasibility arrest unit crab net.This research was executed in January until February 2015 inGalesongSubdistrictTakalarDistrict with MappakalompoVillage aslocation sample. This research use the survey method with the amount sample as much 40 fishermen crab netwho are taken with simple random sampling method.Analysis used by descriptive analysis of investment and financial feasibility analysis that areNet PresentValue (NPV), Net Benefit Cost Ratio(Net B/C) andInternal Rate of Return (IRR). Result of Research indicate that total of investment cost atarrest unit crab net that is equal to IDR 13.414.500with larger investment cost isboat purchasing andarrest unit crab net is feasible to be developedbecause result of financial analysisNPV > 0(IDR177,103,595.7), Net B/C > 1 (13.2)and IRR >interest rate (64%). Key words: catching, fishermen, crab nets, investment, financial feasibility